2008
DOI: 10.1021/ct800347u
|View full text |Cite
|
Sign up to set email alerts
|

First-Principle Calculations of Large Fullerenes

Abstract: State of-the-art density functional theory calculations have been performed for the large fullerenes C180, C240, C320, and C540 using the linear combination of Gaussian-type orbitals density functional theory (LCGTO-DFT) approach. For the calculations all-electron basis sets were employed. All fullerene structures were fully optimized without symmetry constrains. The analysis of the obtained structures as well as a study on the evolution of the bond lengths and calculated binding energies are presented. The fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…Finally, only in recent cases the relative stability compared to the graphene sheet was investigated [19][20][21] at the ab initio level, the limiting factors being either the low level of adopted theory 19 or the small number of investigated members 20,21 .…”
mentioning
confidence: 99%
“…Finally, only in recent cases the relative stability compared to the graphene sheet was investigated [19][20][21] at the ab initio level, the limiting factors being either the low level of adopted theory 19 or the small number of investigated members 20,21 .…”
mentioning
confidence: 99%
“…For example, computation efforts have focused upon predicting structural details for the series of I h fullerenes with 60, 240, 540, 960, 1500, 2160, 2940, 3840, 4860, 6000, 7260, and 8640 carbon atoms in the cage. [3][4][5] Other studies have suggested that large, empty-cage fullerenes may be unusual, low-density materials (bucky balloons). [6,7] Experimental observations of large fullerene-like structures include electron microscopic studies of carbon onions, which appear to consist of concentric shells of fullerene-like cages, [8,9] and mass spectrometric studies on electric arc generated soot, which reveal the presence of carbon clusters with even numbers of atoms up to at least C 600 .…”
mentioning
confidence: 99%
“…Today, we therefore interpret the TOF-MS distribution as linear carbon chains in the region 1 Ä n < 10 [109], macrocyclic rings 10 Ä n < 30 [56,108], and fullerenes n 36 [57]. It is clear that the magic peaks at C 60 and C 70 are not the result of thermodynamic stability, since the cohesion energy of fullerenes continuously increases with the cage size approaching infinity (and thus graphite) [110,111]. Moreover, any fullerene synthesis operates under nonequilibrium conditions with a continuous energy and carbon input.…”
Section: Background and Experimental Synthesismentioning
confidence: 96%
“…To us and others, it was puzzling that only GFs self-assembled in nonequilibrium simulations, although we already mentioned that from a thermodynamic point of view, larger fullerene cages are more stable than smaller ones [110,111] and require less curvature buildup during the cage self-assembly stage. Subsequent heating of [277].…”
Section: Hot Giant Fullerene Shrinkingmentioning
confidence: 98%
See 1 more Smart Citation